2021
DOI: 10.3390/fishes6030024
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Literature, Biodiversity Databases, and Citizen-Science to Reconstruct the Checklist of Chondrichthyans in Cyprus (Eastern Mediterranean Sea)

Abstract: Chondrichthyans are apex predators influencing the trophic web through a top-down process thus their depletion will affect the remaining biota. Notwithstanding that, research on chondrichthyans is sparse or data-limited in several biogeographic areas worldwide, including the Levantine Sea. We revise and update the knowledge of chondrichthyans in Cyprus based on a bibliographic review that gains information retrieved from peer-reviewed and grey literature, Global Biodiversity Information Facility (135 records o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In order to accurately complete the checklist, the available scientific literature and open access databases were also accessed, following the methodology used in Giovos et al (2021) and Giovos et al (2022). The Google Scholar search engine was used to find publications dealing with chondrichthyans in Montenegrin waters in order to find records of additional species belonging to this group.…”
Section: Dataset and Data Sourcesmentioning
confidence: 99%
“…In order to accurately complete the checklist, the available scientific literature and open access databases were also accessed, following the methodology used in Giovos et al (2021) and Giovos et al (2022). The Google Scholar search engine was used to find publications dealing with chondrichthyans in Montenegrin waters in order to find records of additional species belonging to this group.…”
Section: Dataset and Data Sourcesmentioning
confidence: 99%
“…A checklist of 60 chondrichthyans was recently reported by a study which reviewed available data, studies and citizen science reports for the island of Cyprus (Giovos et al, 2021b). A published record of Hexanchus nakamurai (Teng 1962, bigeyed sixgill shark, now H. vitulus, Springer andWaller 1969, Atlantic sixgill shark) has since been retracted (Bengil et al, 2021), while a Cetorhinus maximus (Gunnerus 1785, basking shark) previously reported for Northern Cyprus (Kabasakal, 2013), and for the whole island (Giovos et al, 2021b) was based on a newspaper report which was later found to have been inaccurate, instead being Alopias superciliosus (Lowe 1841, bigeye thresher shark, Hakan Kabasakal pers. comm.).…”
Section: Introductionmentioning
confidence: 99%